An online tomographic sediment trap for high-resolution environmental monitoring - Johansson, Markus; Saarni, Saija; Sorvari, Jouni (Springer Nature, 2026)
Sediment trapping is a well-established method for obtaining information on sedimentation flux and composition in aquatic environments. Passive sediment traps typically have a collection period of several months to a year, while autonomous traps with revolving wheels can achieve a daily time resolution. However, these devices are often costly, require laborious maintenance, and have high power consumption, which limits their use in remote field locations. This study presents a novel, ultra-high-resolution (hourly temporal resolution) sediment trap based on optical tomography that enables continuous online monitoring of sediment flux. Laboratory validation demonstrated a high volumetric calibration accuracy, with a mean measurement error of ± 0.6 mL (R2 = 0.99). We deployed a prototype in Savilahti Bay, Kuopio, to evaluate its ability to detect short-term sediment pulses caused by onshore construction work. The field results confirmed the method’s effectiveness and reliability in tracking highly dynamic flux variations, although image processing techniques require further development for extreme sedimentation rates. The autonomous, solar-powered system transmits data wirelessly, significantly reducing fieldwork requirements. This methodology provides a crucial tool for monitoring high-resolution sediment dynamics and remote study sites.
Keywords: suspended sediment trapping; online technology; environmental monitoring; flux rate; aquatic sediments; construction work impact; water quality